Teaching old dogs new tricks: the effectiveness of community-based social marketing on energy conservation for sustainable university campuses - Aronoff, Jennifer; Champion, Benjamin L.; Lauer, Casey S.; Pahwa, Anil (My University, 2013)
The paper presents a community-based social marketing (CBSM) study that was conducted at Kansas State University (KSU) to determine potential strategies to decrease energy consumption on college campuses. The study was supported by a National Science Foundation (NSF) Research Experience for Undergraduates (REU) project, “Earth, Wind, and Fire: Sustainable Energy for the 21st Century.” The ultimate goal of this research is to establish an effective campaign to make KSU a more sustainable community while ensuring that the needs and concerns of individuals-specifically, laboratory scientists-on campus are addressed as well. This approach to sustainability has the capability of motivating and empowering building users and managers to not only make KSU's campus more sustainable but also to stretch beyond the boundaries of the university in the future.
Keywords: Community-based social marketing; Sustainability; Energy conservation; College campuses